Hubungan Kelengkapan Imunisasi Dengan Status Kesehatan Anak Usia 1-2 Tahun - Nursyahid Siregar; Evi Arnawati (Poltekkes Kemenkes Denpasar, 2022)
ABSTRACTThe health status of toddlers in general can affect the growth and development of toddlers in general. So it is necessary to be fully immunized so that it does not get sick easily. Sub-Puskesmas Sebulu Modern's total immunization achievement is not yet 100%; each month, children are treated for various diseases. The purpose of this study is to determine the completeness of immunization with respect to the health status of children aged 1-2 years. This type of research is an analytic survey using a prospective cohort design. The population is mothers with children aged 1-2 years at the Sebulu Modern Health Center, totaling 63 people. Using slovin, a sample of 54 people was obtained. The sampling technique used was consecutive sampling. Data analysis using Chi-Square. The characteristics of respondents are mostly mothers aged 26–30 years (44.4%), graduated from high school (61.1%), household members (42.6%), and children aged 13–24 months (81.5%), female (55.6%), body weight (7–11 kg and 12–16 kg (46.3%), and body length 81–90 cm (51.9%). Complete immunization (63%), and overall health (61.1%) There is a relationship between the completeness of immunization and the health status of children aged 1-2 years (p value: 0.000 0.05).ABSTRAKStatus kesehatan balita secara umum dapat mempengaruhi pertumbuhan dan perkembangan balita secara umum. Maka perlu diberikan imunisasi lengkap sehingga tidak mudah sakit. Puskesmas Pembantu Sebulu Modern capaian imunisasi lengkap belum 100%, tiap bulan masih terdapat anak berobat dengan berbagai penyakit. Tujuan peneltian ini untuk mengetahui kelengkapan imunisasi dengan status kesehatan anak usia 1-2 tahun. Jenis penelitian ini survey analitik menggunakan desain kohort prospektif. Populasi adalah ibu memiliki anak usia 1-2 tahun di Puskesmas Pembantu Sebulu Modern berjumlah 63 orang, menggunakan slovin diperoleh sampel berjumlah 54 orang. Teknik pengambilan sampel menggunakan consecutive sampling. Analisa data menggunakan Chi-Square. Karakteristik responden sebagian besar ibu dengan umur 26-30 tahun (44,4%), tamat SMA (61,1%), IRT (42,6%), sedangkan anak umur 13-24 bulan (81,5%), perempuan (55,6%), berat badan 7-11 kg dan 12-16 kg (46,3%) dan panjang badan 81-90 cm (51,9%). Imunisasi lengkap (63%) dan sehat (61,1%). Ada hubungan kelengkapan imunisasi dengan status kesehatan anak usia 1-2 tahun (p-value: 0,000α:0,05).